ARCHETYPES AND ROMANTICISM IN ESTABLISHING NATIONAL IDENTITY AS REFLECTED IN TOLKIEN’S THE SILMARILLION: REFLECTED IN TOLKIEN’S THE SILMARILLION Emil Eka Putra, emilekaputra@gmail.com, Universitas Putera Batam - Emil eka Putra (BASIS (Bahasa dan Sastra Inggris), 2014)
This research demonstrates the relationship of fantasy fiction, archetypes, romanticism and nationalism in one of fantasy fiction, namely Tolkien’s The Silmarillion. Since fantasy fiction, with the stereotype of escapism, is less appreciated this article is written in attempt to give more appreciation to fantasy fiction. Analysis to show the relationship of fantasy fiction, archetype, romanticism and nationalism is carried out by applying archetypal approach and Frye’s concept of mythos. This analysis is aimed at determining the position of the story in Frye’s mythos taxonomy and its values. The values, then, are compared with values found in English nationalistic discourse. The result of this analysis indicates that the story of The Silmarillion can be classified as tragic mythos. However, tragedy in the Silmarillion is elaborated differently from the characteristics of the mythos suggested by Frye. Tragedy of The Silmarillion is collective in its nature. The uniqueness of tragedy in The Silmarillion, then, is read as representation of fellowship spirit value in English nationalistic discourse. The Silmarillion also shows wisdom and historical continuity values parallel with values found English nationalistic discourse. From these values The Silmarillion shows that pastoral life with its collectivity, wisdom and tranquility as an ideal life for English people. Further, the revealed values also shows that in establishing England national identity, Tolkien, like his national identity builders predecessor, refers to old wisdoms. He refers to values that are perceived as part of values in previous past gloriuos era. By doing so it can be concluded that in establishing the national identity Tolkien uses the same method with his predecessor; refering back to the previous golden era—a kind of romanticism.